Effective strategies for teachers to guide children’s art activities: based on a survey of children’s art activities and teacher guidance, and an analysis of their correlation - Zhang, Han; Yang, Yifan; Li, Jialin (Frontiers in Psychology, 2025)
Providing effective strategic guidance for teachers to guide children’s art activities and improving the quality and level of children’s art activities is of great significance for children’s mental development and subsequent development, as well as improving the quality of teacher teaching. We developed a children’s art activity and teacher guidance observation table to collect art activity data from 538 children and guidance behavior data from 62 kindergarten teachers in 10 kindergartens in Chongqing, Sichuan, Hubei, Jiangxi, Jiangsu, and Shanghai. Then, we analyzed the differences in children’s art activities and discussed the correlation between children’s art activities and teachers’ guidance. The results showed that there are significant and extremely significant differences in the art activity styles and interests of children in random activities, independent activities, and organized activities. There is a significant correlation between teacher guidance and children’s art interaction styles. Based on the above results, we suggest that when instructing children’s art activities, teachers should build a hierarchical and interesting learning environment to stimulate children’s interest in learning art and make it fun, to continuously improve the quality and level of children’s art activities.